2004
DOI: 10.1191/0961203304lu2001oa
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid antibodies as cause of pregnancy loss

Abstract: Antiphospholipid antibodies detected by lupus anticoagulant, anticardiolipin or anti-beta2 glycoprotein I assays were associated with fetal loss. Rather than being diagnostic tools only, antiphospholipid antibodies are thought to be pathogenic. The strongest demonstration of their pathogenic role lies in the ability to induce fetal resorptions--the experimental equivalents of the human fetal losses--when passively infused in pregnant naive animals. However, still debated is how the antibodies might induce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 34 publications
3
34
1
2
Order By: Relevance
“…The production of trophoblast-specific proteins (human chorionic gonadotropin) and adhesion molecules (α1 and α5 integrins, as well as E and VE cadherins) was also reduced [18,19]. Certain antibodies, such as those against annexin V, were also shown to induce trophoblast apoptosis [3]. These effects have recently been confirmed by the use of placental explant cultures, where it was shown that aPL antibodies increased placental apoptosis, decreased villous trophoblast proliferation and reduced extra villous trophoblast invasion through matrigel [20].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 94%
See 4 more Smart Citations
“…The production of trophoblast-specific proteins (human chorionic gonadotropin) and adhesion molecules (α1 and α5 integrins, as well as E and VE cadherins) was also reduced [18,19]. Certain antibodies, such as those against annexin V, were also shown to induce trophoblast apoptosis [3]. These effects have recently been confirmed by the use of placental explant cultures, where it was shown that aPL antibodies increased placental apoptosis, decreased villous trophoblast proliferation and reduced extra villous trophoblast invasion through matrigel [20].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 94%
“…Although these antibodies have been shown to bind to a wide variety of membrane phospholipids (e.g. cardiolipin and phosphatidyl serine), they do not appear to bind directly to phospholipid but rather to phospholipid-binding proteins or to phospholipid/phospholipid-binding protein complexes [3,15]. One of these proteins is beta 2 glycoprotein (β2GPI), which is localised on extravillous cytotrophoblast and syncytiotrophoblast [15,16].…”
Section: Preeclampsia: An Immune Disorder?mentioning
confidence: 99%
See 3 more Smart Citations